Dissemination and perception of adaptation co-benefits: Insights from the coastal area of Bangladesh. (December 2020) - Rahman, Syed Mahbubur; Mori, Akihisa
Highlights: Research about adaptation co-benefits is limited; most of the literature focuses on mitigation. Community people, NGOs and government officials possess deviated perceptions about adaptation co-benefits. Project implementers do not sufficiently communicate co-benefits an intervention may generate. Awareness about adaptation co-benefits has the potential to overcome the challenges posed by the adaptation paradox. Abstract: The assessment and evaluation of co-benefits related to climate change policy has shifted from a mitigation-centric approach to also include adaptation. In 2017, the 23rd Conference of the Parties of the United Nations Framework Convention on Climate Change requested that Parties submit proposals for assessing adaptation co-benefits along with their adaptation and resilience strategies. However, adaptation co-benefits are not always noticed during the initial stage of risk reduction measures, and this can become a bottleneck for intervention. Against this backdrop, this research aims to explore how stakeholders recognize and communicate the co-benefits of adaptation interventions, by conducting a case study of Barguna Sadar, a shoreline upazila (sub-district) in the southern part of Bangladesh that is highly vulnerable to the impacts of climate change. This qualitative study involved focus group discussions and interviews with stakeholders. The results revealed a lack of awareness and understanding of adaptation co-benefits among community members, especially the intended beneficiaries, related to projects implemented by local and international non-government organizations. Insufficient communication prior to the implementation of adaptation projects was found to be the underlying cause of this lack of awareness. Improving public awareness of adaptation co-benefits has the potential to overcome the challenges posed by the adaptation paradox.